Piezoelectric and electromagnetic hybrid micro-energy harvester for wireless electronic devices - Hablee, Mohammad Alif Akhirudin; Mohamad Hanif, Noor Hazrin Hany; Mohd Ismail, Mohd Ismifaizul (IEEE, 2026)
Energy harvesting offers the potential to convert ambient vibrations into usable electrical energy, thus enabling the self-powered operation of electronic devices and reducing reliance on traditional batteries. However, existing hybrid harvesters face challenges in harnessing and converting ambient vibrations effectively. Design limitations, including restricted bandwidth frequency and power losses during conversion hinder their efficiency. This study explored a hybrid energy harvester using dual PZT −5H bimorph cantilevered piezoelectric beams and wound coils. To optimize voltage output, adding proof mass and different beam arrangements were tested, along with frequency sweeps. Repulsive magnets were used to fine-tune the frequency, while impedance matching maximized power transfer. The results reveal that adding proof mass, a series connection, and a stacked arrangement of the beams increased the AC voltage. The harvester reached its peak performance of 16.79V at resonance. This high voltage was maintained at 30Hz but dropped notably at 60Hz. After rectification, the 12V AC at 18Hz yielded an 8.31V DC, which approximately aligns with theoretical expectations.